1999
DOI: 10.1053/euhj.1999.1483
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lovastatin on progression of non-dilated and dilated coronary segments and on restenosis in patients after PTCA. The Cholesterol Lowering Atherosclerosis PTCA Trial (CLAPT)

Abstract: Lovastatin reduced the progression of dilated lesions in men with elective PTCA. Independent of treatment allocation, the dilated lesions regressed and the non-dilated segments progressed during the study follow-up. Four weeks of pre-treatment with lovastatin did not influence the rate of restenosis. Lovastatin had no statistically significant effect on non-dilated segments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0
4

Year Published

2004
2004
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 35 publications
1
28
0
4
Order By: Relevance
“…Most trials (nϭ21, 91%) had Jadad scores of Ն3; only 2 had a lower Jadad rating. 27,28 Few patients were lost to follow-up (median, 0.09%; IQR, 0.01%-0.46%). The median LDL cholesterol reduction achieved was 1.03 mmol/L (IQR, 0.93-1.36 mmol/L).…”
Section: Randomized Trialsmentioning
confidence: 99%
“…Most trials (nϭ21, 91%) had Jadad scores of Ն3; only 2 had a lower Jadad rating. 27,28 Few patients were lost to follow-up (median, 0.09%; IQR, 0.01%-0.46%). The median LDL cholesterol reduction achieved was 1.03 mmol/L (IQR, 0.93-1.36 mmol/L).…”
Section: Randomized Trialsmentioning
confidence: 99%
“…Moreover, most trials have shown that statins have no or weak effects on the rate of restenosis. [46][47][48] We certainly agree on the non-beneficial effect of statins on restenosis because our histological examination also showed that statins did not reduce the proliferation of SMC. However, they did reveal that statins have antithrombotic effects, even in ISR tissue, and may induce beneficial effects on thrombosis and thrombotic events after stent implantation.…”
Section: Study Limitationsmentioning
confidence: 74%
“…Para estudar a interferência da redução do LDL-c (colesterol ligado à LDL) nas lesões ateroscleróticas das artérias coronárias, avaliadas por angiografia, as vastatinas foram utilizadas isoladamente ou associadas a outros fármacos hipolipemiantes ou a afé-rese [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] (tab. I).…”
Section: A -Estudos Controlados Por Angiografiaunclassified
“…
264 nose e não melhorou significantemente os outros parâmetros angiográficos 16,[18][19][20]25 . Resultados alentadores foram obtidos após a implantação de "stents" em estudos não randomizados 26 .
B -Estudos controlados por métodos não invasivos 27-32

Ultra-sonografia e, mais recentemente, ressonância magnética de alta resolução têm sido empregadas para avaliar a ação das vastatinas na aterosclerose das artérias carotídeas.

…”
unclassified
See 1 more Smart Citation